Development of an electrical impedance tomography system for imaging and measurement applications - Salama, Abdalla Mohamed Ahmed Mahmoud (2025)
Electrical impedance tomography (EIT) is a non-invasive imaging technique that reconstructs the internal conductivity distribution of a medium using voltage or current measurements obtained via electrodes. Despite its potential, conventional EIT systems face challenges such as hardware complexity, high computational demands, and limited adaptability for diverse applications. This research addresses these limitations by developing a novel EIT system, termed Single-Ended Electrical Impedance Tomography (SEEIT), which introduces significant advancements in both hardware design and measurement methodology.